Community Sport Events and CSR Sponsorship: Examining the Impacts of a Public Health Agenda. (December 2016) - Batty, Rachel J.; Cuskelly, Graham; Toohey, Kristine
Tobacco and alcohol companies have long faced criticism regarding the unhealthy nature of their products and decisions to sponsor community sport events (CSEs). Recent public health concerns have led to additional CSE sponsor products facing similar criticism, including soft drinks, confectionary, and fast food. With CSE sponsorship increasingly utilized as a corporate social responsibility (CSR) initiative, research into the perceptions, effects, and management of CSR-based sponsorships within CSEs is opportune. This multiple case study reviews the food and beverage sponsorships of four New Zealand–based CSEs and positions resulting discourse within the sport management domain. Findings suggest that criticism of CSR-based CSE sponsorship is on the rise and predominantly stems from public health concerns. Such ongoing criticism of sponsorship decisions could be detrimental to the financial viability of CSEs.